Eksemplarisk usedelighet - Eriksen, Anne (Tidsskrift for kulturforskning, 2018)
"Some examples" is the title of the opening chapter of Eilert Sundt's large work Om sædeligheds-tilstanden (1857). Sundt asks whether the examples that he presents - short descriptions of his encounters with persons, mainly from the lower rural population, who had childÂren born out of wedlock - contain true and reliable information? His own answer is janus-faced. He presents strong arguments for the use of quantitative analyses in social research, but he also starts each of the following chapters of his book with new examples. â€‚â€‚â€‚Assisted by John D. Lyons' theories about how examples work in texts, this article investigates Sundt's use of them. Examples are not only introductory anecdotes in his work, to be corrected by the more "scientific" quantitative analysis, as his own words may indicate. Examples are also used to produce pathos, to convey morality, to persuade the readers of Sundt's interpretations and, perhaps most important of all, to create an image of "the people", the Other, the group that is being subjected to the then new science of sociology.